2018
DOI: 10.1016/j.apsoil.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous application of two herbicides and green compost in a field experiment: Implications on soil microbial community

Abstract: Highlights  Effects of herbicides and green compost on soil microbiology were evaluated at field scale  Green compost decreased the dissipation rate of triasulfuron, but no that of prosulfocarb  Combined application of triasulfuron and prosulfocarb modified soil microbial community  Green compost buffered the effects of herbicides on soil microbial activity and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 51 publications
(73 reference statements)
3
25
1
Order By: Relevance
“…No significant changes in DHA were observed simultaneously to the dissipation of herbicides applied as observed in S + H, and a non-significant relationship was found between herbicide residues and DHA values in the amended soils. This was probably due to the combination of herbicides applied with different adsorption and bioavailability rates in the amended soils, and the long persistence of some of them to produce more toxic effects on soil microbial biomass and activity than the single application of individual compounds [3,13]. Previous studies have reported this trend for one of the herbicides used here, namely, diflufenican, which mixed with glyphosate or with mesosulfuron-methyl and iodosulfuron methyl-sodium decreased DHA and other enzymatic activities [18,26].…”
Section: Soil Dehydrogenase Activity (Dha)mentioning
confidence: 99%
See 3 more Smart Citations
“…No significant changes in DHA were observed simultaneously to the dissipation of herbicides applied as observed in S + H, and a non-significant relationship was found between herbicide residues and DHA values in the amended soils. This was probably due to the combination of herbicides applied with different adsorption and bioavailability rates in the amended soils, and the long persistence of some of them to produce more toxic effects on soil microbial biomass and activity than the single application of individual compounds [3,13]. Previous studies have reported this trend for one of the herbicides used here, namely, diflufenican, which mixed with glyphosate or with mesosulfuron-methyl and iodosulfuron methyl-sodium decreased DHA and other enzymatic activities [18,26].…”
Section: Soil Dehydrogenase Activity (Dha)mentioning
confidence: 99%
“…This practice is often used to increase crop yields, improve soil quality and fertility, preserve the soil from degradation, mitigate pesticide leaching, and enhance soil microbial activity [6,11]. Organic residues with a potential value are those from agricultural, industrial, and urban activities, such as the composted spent mushroom substrate (SMS) and green compost (GC) [12,13]. The OM of these residues may modify the persistence, dynamics, and environmental fate of herbicides applied to amended soils [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some authors have reported no response (see Maughan et al, ; Teat, Neufeld, Gehl, & Gonzales, ), recently the balance of evidence suggests that fertilizer increases yields (Chen et al, ; Wang, Smyth, Crozier, Gehl, & Heitman, ; Xu, Gauder, Gruber, & Claupein, ). Emissions of the powerful greenhouse gas (GHG) nitrous oxide (N 2 O), derived from N fertilizer, are the biggest source of GHGs from agriculture after livestock methane (CH 4 ; FAO, ), and the use of fertilizer and composts can also lead to increased soil respiration ( R s ; Garcia‐Delgado et al, ; Ozlu & Kumar, ) and CH 4 emissions (Fernandez‐Luqueno et al, ; Thangarajan, Bolan, Tian, Naidu, & Kunhikrishnan, ), two other important components of a net GHG balance. Previous work has shown that GHG emissions, and especially N 2 O fluxes, from Miscanthus are much lower than conventional crop rotations (Drewer, Finch, Lloyd, Baggs, & Skiba, ), and this is key to its viability as a bioenergy crop (Whitaker et al, ).…”
Section: Introductionmentioning
confidence: 99%